The core skills of the cio we need (2010)
Currently, organizations depend on their Information Systems and Technology Systems (IS/IT) functioning normally, as well as the innovative processes that can arise from them. However, the current performance of the CIO (Chief Information Officer) can be questioned when one contrasts his role as the one responsible for the administration of opportunities given by IS/IT, and the business value added by those technologies. In such a scenario, we pose the question of how the IS/IT professionals acquire articulated competencies and skills that prepare them for the CIO position. In order to elucidate an answer to our question, we interviewed professionals in the CIO position, and surveyed an array of prestigious graduate programs from the USA, European Union and Asia. The most relevant findings of our study report an operational view towards the CIO in the academic formation as well as in the roles that organizations assign to the professional.